gA and gB glycoproteins of herpes simplex virus type 1: two forms of a single polypeptide. - Eberle, R (1980)
Utilizing a combination of preparative sodium dodecyl sulfate-polyacrylamide gel electrophoresis and sodium dodecyl sulfate-hydroxylapatite column chromatography, we have separated and purified the gA and gB glycoproteins of the major virus-specific glycoprotein region from herpes simplex virus type 1-infected cells. By using purified antigen preparations, antisera specific to each of these glycoproteins were produced. Immunoprecipitation from detergent extracts of infected cells and radioimmune precipitation of the purified antigens have shown that the anti-gA and anti-gB sera each recognize both the gA and the gB glycoproteins. The anti-gA serum was also shown to neutralize virus despite the presence of only minute quantities of the gA glycoprotein in virions. Pulse-chase studies have indicated that the gA and gB glycoproteins are synthesized from a common precursor polypeptide. Together, these data demonstrate that the gA and gB glycoproteins of herpes simplex virus type 1 are antigenically similar but not identical and probably represent two different forms of the same polypeptide which differ in their degree of glycosylation.